How to achieve and sustain fiscal discipline in Turkey: Rising Taxes, reducing government spending or a combination of both? - Ayşe Kaya; Hüseyin Şen (Romanian Journal of Fiscal Policy (RJFP), 2013)
The main purpose of this paper is to investigate the relationship between tax revenue and government spending in order to make some policy suggestions on how to achieve fiscal discipline in Turkey. We have used the cointegrated vector autoregression (VAR) method along with the Granger causality test (1969). The empirical findings indicate that there is a uni-directional causality running from spending to tax revenue. In other words, our findings support the spend-and-tax hypothesis for fiscal discipline in Turkey over the period of 1975 - 2011. Since there is a uni-directional causality, running from government spending to tax revenue, spending restrictions are required to reduce budget deficits, and reducing government spending is a better solution than increasing tax revenue to obtain optimal fiscal discipline in Turkey.
Keywords: E62; H62; 330; Fiscal Discipline; Fiscal Policy; Government Revenue; Government Expenditure; Causality Test